Aggregation-Induced Emission-Active Cyanostilbene-Based Liquid Crystals: Self-Assembly, Photophysical Property, and Multiresponsive Behavior - Bian Li; Junde Zhang; Juan Wang; Xiaofang Chen (Molecules)
Cyanostilbene (CS)-related conjugated groups can be considered as dual functional groups of AIEgen and mesogen to construct photoluminescent liquid crystals, and it is essential to study the relationship between their molecular structures and compound properties systematically. In this paper, we designed and synthesized linear and bent-shaped CS derivatives containing ester- and amide-connecting groups and different substituted numbers of alkoxy tails. Their phase behaviors and photophysical properties were investigated in depth. The bent-shaped compounds with the mono-substituted alkoxy tail exhibit a smectic C structure, and those containing two or three alkoxy tails possess a hexagonal columnar phase structure. The compounds exhibit aggregation-induced emission (AIE) properties in tetrahydrofuran (THF)/water mixtures. When the water fraction increases to a certain threshold, a dramatic increase in emission intensity and a red-shift in the fluorescence emission peak are detected. The emission peaks of the ester-type compounds in solid states are around 480 nm, and those of the amide-type compounds are extended to 590 nm, exhibiting versatile luminescent colors. Moreover, thermochromic and photochromic fluorescence-responsive properties are witnessed in these CS derivatives. This work provides a new strategy for the design and synthesis of fluorescent liquid crystalline materials with multiple response properties.